Penerapan Konsep Full Pedestrian Mall pada Koridor Perdagangan Studi Kasus : Jalan Soeprapto Kota Gorontalo - Fendy Faizal Gobel (Gorontalo Journal of Infrastructure and Science Engineering, 2018)
The street space in the trading corridor looks irregular. This is because public space is contested by many parties, such as road users, street hawkers, pedestrians and parking users as well as formal traders. This encourages the birth of behavior adaptation to the environmental changes that occur, so as to establish the business territoriality to reinforce the physical and non-physical boundaries that have the potential to cause conflict territory use of public space. This study aims to design the trade corridor with full pedestrian mall concept so as to create a safe and comfortable shopping space. From this research is expected to be obtained steps to reduce conflict and optimize function of the space. Object of research in the form of observation of public space component that is physical setting of space (milleu), setting activity (activity) and human behavior (social setting). The method used is qualitative with Rationalistic approach. At the design stage do the design experiment with trial and error of design concept through transformation process until the embodiment of the formation in 2 or 3 dimension.